Perspectives of using Illumina MiSeq for identification of arbuscular mycorrhizal fungi - A. A. Kryukov; A. O. Gorbunova; E. M. Machs; Y. V. Mikhaylova; A. V. Rodionov; P. M. Zhurbenko; A. P. Yurkov (Вавиловский журнал генетики и селекции)
Arbuscular mycorrhiza fungi (AMF) form one of the most common symbiosis with the majority of land plants. AMF supply the plant with various mineral elements, primarily phosphorus, and improve the water supply. The search for the most effective AMF strains for symbiosis and the creation of microbial preparations on that basis is an important task for modern biology. Owing to the difficulties of cultivation without a host plant and their high genetic polymorphism, identifying AMF is very difficult. The high number of cryptic species often also makes morphological identification unreliable. Recent years have seen growth in the number of AMF biodiversity studies performed by modern NGS-based methods, Illumina MiSeq in particular. Currently, there are still many questions that remain for the identification of AМF. The most important are whether conservative or variable sequences should be used to select a marker for barcoding and whether universal primers or those specific to AMF should be used. In our work, we have successfully used universal primers ITS3 and ITS4 for the sequencing in Illumina MiSeq of the 5.8S rDNA – ITS2 region of the 35S rRNA genes, which contain both a conservative and variable regions. The molecular genetic approach for AMF identification was quite effective and allowed us to reliably identify eight of nine isolates to the species level: five isolates of Rhizophagus irregularis, and one isolate of R. invermaius, Paraglomus laccatum, and Claroideoglomus etunicatum, respectively. For all five R. irregularis isolates high variability in the ITS region and the absence of ecotopic-related molecular characters in the ITS2 region were demonstrated. The NCBI data is still insufficient for accurate AMF identification of Acaulospora sp. isolates from the genus to the species level.